Characterizing the radial oxygen abundance distribution in disk galaxies - Zinchenko, Igor A.; Just, Andreas; Pilyugin, Leonid S.; Lara-Lopez, Maritza Arlene (Astronomy and astrophysics, 2019)
The relation between the radial oxygen abundance distribution (gradient) and other parameters of a galaxy such as mass, Hubble type, and a bar strength, remains unclear although a large amount of observational data have been obtained in the past years.Aims. We examine the possible dependence of the radial oxygen abundance distribution on non-axisymmetrical structures (bar/spirals) and other macroscopic parameters such as the mass, the optical radius R25, the color g − r, and the surface brightness of the galaxy. A sample of disk galaxies from the third data release of the Calar Alto Legacy Integral Field Area Survey (CALIFA DR3) is considered.Methods. We adopted the Fourier amplitude A2 of the surface brightness as a quantitative characteristic of the strength of non-axisymmetric structures in a galactic disk, in addition to the commonly used morphologic division for A, AB, and B types based on the Hubble classification. To distinguish changes in local oxygen abundance caused by the non-axisymmetrical structures, the multiparametric mass-metallicity relation was constructed as a function of parameters such as the bar/spiral pattern strength, the disk size, color index g − r in the Sloan Digital Sky Survey (SDSS) bands, and central surface brightness of the disk. The gas-phase oxygen abundance gradient is determined by using the R calibration.Results. We find that there is no significant impact of the non-axisymmetric structures such as a bar and/or spiral patterns on the local oxygen abundance and radial oxygen abundance gradient of disk galaxies. Galaxies with higher mass, however, exhibit flatter oxygen abundance gradients in units of dex/kpc, but this effect is significantly less prominent for the oxygen abundance gradients in units of dex/R25 and almost disappears when the inner parts are avoided (R > 0.25R25). We show that the oxygen abundance in the central part of the galaxy depends neither on the optical radius R25 nor on the color g − r or the surface brightness of the galaxy. Instead, outside the central part of the galaxy, the oxygen abundance increases with g − r value and central surface brightness of the disk.
Gesehen am 10.04.2019